Significance of obstetric Doppler studies in prediction of perinatal outcome in pregnancy induced hypertension - Gaikwad, Pradip R.; Gandhewar, Manisha R.; Rose, Nity; Suryakar, Vidyadhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy induced hypertension (PIH) is associated with adverse perinatal outcome. Multi vessel color Doppler studies are useful in these cases for timely intervention. The aim of present study was to know the significance of umbilical, middle cerebral and uterine artery Doppler studies in PIH and to analyse its role in predicting perinatal outcome. Methods: This was a prospective study of 106 singleton pregnancies in the third trimester with PIH. The results of last Doppler ultrasound within one week of delivery were used for analysis. Adverse perinatal outcome was studied in the form of emergency cesarean section for fetal distress, meconium stained amniotic fluid, Apgar at 5 min <7, NICU admission and perinatal mortality (stillbirths and neonatal death). Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of various Doppler parameters were calculated after comparing with standard. Results: In the present study specificity and diagnostic accuracy of all Doppler ultrasound parameters was high in predicting adverse perinatal outcome. Cerebroplacental ratio showed highest specificity (98.55%), PPV (94.44%) and diagnostic accuracy (80.19%) in predicting adverse perinatal outcome and it is better than MCA PI and UA PI alone. Uterine artery Doppler evaluation also gives additional information in predicting adverse perinatal outcome. Conclusions: Amongst various Doppler parameters cerebroplacental index (MCA/UA PI) is best predictor of adverse perinatal outcome.